1997
DOI: 10.1183/09031936.97.10020308
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of protein kinase C in lymphocytes in asthma: possible mechanism of regulation

Abstract: Asthma is an inflammatory disease of the airways. Activation of lymphocytes leads to elaboration of inflammatory mediators which are likely to initiate and perpetuate the asthmatic response. During activation of lymphocytes, the role of protein kinase C (PKC) has been emphasized. Therefore, changes in PKC activity in peripheral blood lymphocytes in bronchial asthma can be expected, which may be due to alterations in the regulatory mechanisms of the enzyme molecule. To understand the mechanism of regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Previously, several investigators have suggested that PKC plays an active role in the progression and exacerbation of asthma [16,17]. We have also demonstrated acerbation of asthma [16,17]. We have also demonstrated that PKC antagonist sphingosine reduced the T lymphocytes activity isolated from asthmatic patients [16].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Previously, several investigators have suggested that PKC plays an active role in the progression and exacerbation of asthma [16,17]. We have also demonstrated acerbation of asthma [16,17]. We have also demonstrated that PKC antagonist sphingosine reduced the T lymphocytes activity isolated from asthmatic patients [16].…”
Section: Discussionmentioning
confidence: 59%
“…We, therefore, investigated the biochemical changes in airway hyper reactive guinea pig model of asthma and have presented evidence that PKC isoenzymes could be key mediators in the initiation of airway hypersensitivity during the onset of asthma. Previously, several investigators have suggested that PKC plays an active role in the progression and exacerbation of asthma [16,17]. We have also demonstrated acerbation of asthma [16,17].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It has been previously demonstrated that histamine H1 receptors can signal to the nucleus through the PKC [46] and consequently the effects of H1 receptors are PKC dependent. Elevated PKC levels were observed in lymphocytes of asthmatic patients and histamine reportedly exerted its action on the PKC activity by modulating the regulatory domain of the enzyme [47].…”
Section: Discussionmentioning
confidence: 99%
“…The pellet containing lymphocytes was washed twice with physiological saline. Contaminating erythrocytes were removed by giving osmotic shock to the pellet by the method of Bansal et al [37]. The cell suspension was centrifuged again, the pellet washed twice with physiological saline and resuspended in physiological saline.…”
Section: Preparation Of Serum and Lysate Of Lymphocytes And Erythrocytesmentioning
confidence: 99%